The Influence of Audit Opinion, Auditor Switching, and Number of Audit Committees on Audit Report Lag - Brandon Christian Tomasila; Hisar Pangaribuan (Ilomata International Journal of Tax and Accounting, 2023)
Despite the fact that listed firms must abide by standards set forth by the Indonesia Stock Exchange (IDX) to submit audited financial reports and publish them, it has not reduced the number of companies that do not publish their financial reports in accordance with the applicable rules. As of February 2023, a total of 32 issuers have been sanctioned for late publication of their financial reports. A high audit report lag Table results in inaccurate and outdated financial information. This research's main goal is to prove how the number of audit committees, the number of audit opinions, and auditor change may affect how long it takes to produce an audit report. A quantitative research approach utilizing secondary data is employed for this investigation. The research focuses on manufacturing and transportation firms publicly traded on the IDX during the years 2020-2021. The sample size encompasses 160 companies, spanning a 2-year research period and yielding 320 data points. The analysis' conclusions show that audit opinion has a big impact on the audit report lag; in contrast, auditor switching and the number of audit committees do not have a substantial influence on this duration. The researcher recommends that future studies consider broadening the scope of the research population to enhance result accuracy and incorporate a more diverse sample.